Penerapan Teknik Seo (Search Engine Optimization) pada Website Pikiran-Rakyat.Com dalam Strategi Pemasaran - Urmila Urmila; Erwan Sastrawan; Harnida Wahyuni Adda (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The website is one of the information media that is available quickly and supports the company's business. However, sales through the website must be supported by implementing a marketing strategy. This study aims to apply Search Engine Optimization (SEO) techniques to the Pikiran-rakyat.com website in a marketing strategy to optimize the website and increase visitors. This research methodology uses the SEO Web Design Methodology with on-Page SEO and Off-Page SEO criteria. The results of implementing SEO techniques carried out on the Pikiran-rakyat.com website yield results in the form of an optimal website in placing the website's position in search engines on the first page of Google.